2017
DOI: 10.1073/pnas.1708518114
|View full text |Cite
|
Sign up to set email alerts
|

Distress and rumor exposure on social media during a campus lockdown

Abstract: SignificanceDuring active shooter events when danger is imminent and official information is disseminated inconsistently, ambiguity is high. In these situations, individuals may seek information from unofficial channels (e.g., social media), thereby exposing themselves to unverified information and rumors. In a study of students caught in a university-wide lockdown, we found that those who relied on social media for updates reported increased exposure to conflicting information. Moreover, those who trusted wha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 125 publications
(110 citation statements)
references
References 30 publications
2
99
0
2
Order By: Relevance
“…In the COVID-19 emergency, medical workers in Wuhan have been dealing with high risk of infection and inadequate protection against contamination, overwork, frustration, discrimination, isolation, patients with negative emotions, a lack of contact with their families and exhaustion (Kang et al, 2020). The current situation is causing mental health problems such as stress, anxiety, depressive symptoms, insomnia, denial, anger and fear (Jones et al, 2017). These mental health problems not only affect attention, understanding and decision-making capacity of medical workers, which could hinder the fight against COVID-19, but they could also have a lasting effect on their overall well-being (Kang et al, 2020).…”
Section: Covid-19 and Consequences For Mental Healthmentioning
confidence: 99%
“…In the COVID-19 emergency, medical workers in Wuhan have been dealing with high risk of infection and inadequate protection against contamination, overwork, frustration, discrimination, isolation, patients with negative emotions, a lack of contact with their families and exhaustion (Kang et al, 2020). The current situation is causing mental health problems such as stress, anxiety, depressive symptoms, insomnia, denial, anger and fear (Jones et al, 2017). These mental health problems not only affect attention, understanding and decision-making capacity of medical workers, which could hinder the fight against COVID-19, but they could also have a lasting effect on their overall well-being (Kang et al, 2020).…”
Section: Covid-19 and Consequences For Mental Healthmentioning
confidence: 99%
“…The unmoderated nature of social media user's posting behavior might lead to the accumulation of invalidated and unverified information and news involving speculation and uncertainty regarding social events (Ye et al 2018a, b). Jones et al (2017) found those who relying on social media for updates of a campus lockdown tend to suffer from greater distress due to their increased exposure to conflicting content in social media channels. Rumors are considered messages or forms of interaction among people about certain events that may not be true.…”
Section: Rumorsmentioning
confidence: 99%
“…In contrast, in another article, the authors recommended against the use of social media because of the negative emotions associated with users during these incidents. For example, their survey responses revealed that individuals who used social media as their primary source of information were more likely to be under greater distress as a result of rumor transmission (Jones, Thompson, Schetter, & Silver, ). In another article, the authors went further, stating that there should be rules and social media monitoring developed for these scenarios to limit misinformation and rumors (Mazer et al., ).…”
Section: Resultsmentioning
confidence: 99%